The drama is coming now : the theater criticism of Richard Gilman, 1961-1991 - Gilman, Richard, 1923-2006 (Yale University Press, 2005)
This engrossing book presents the first collection in more than three decades of one of America's finest drama critics. Richard Gilman chronicles a major period in American theatre history, one that witnessed the birth or spread of Off-Broadway, regional theatre, nonprofit companies, and avant-garde performance, as well as growing interest in plays by women and minorities and in world drama. His writing, however, is more than a revealing look at an era. It is criticism for the ages. Insightful, provocative, and impassioned, the articles represent the full range of Gilman's interests. There are essays, profiles, and book reviews dealing with such topics as the "new naturalism" in theatre, Brecht's collected plays, and the legacy of Stanislavski. There is also a generous sampling of Gilman's comments on plays by O'Neill, Miller, Chekhov, Albee, Ibsen, Anouilh, Beckett, Ionesco, Pinter, Fugard, and many others